In Vivo Restoration of Myocardial Conduction With Carbon Nanotube Fibers. (August 2019) - McCauley, Mark D.; Vitale, Flavia; Yan, J. Stephen; Young, Colin C.; Greet, Brian; Orecchioni, Marco; Perike, Srikanth; Elgalad, Abdelmotagaly; Coco, Julia A.; John, Mathews; Taylor, Doris A.; Sampaio, Luiz C.; et al.
Abstract : Background: Impaired myocardial conduction is the underlying mechanism for re-entrant arrhythmias. Carbon nanotube fibers (CNTfs) combine the mechanical properties of suture materials with the conductive properties of metals and may form a restorative solution to impaired myocardial conduction. Methods: Acute open chest electrophysiology studies were performed in sheep (n=3). Radiofrequency ablation was used to create epicardial conduction delay after which CNTf and then silk suture controls were applied. CNTfs were surgically sewn across the right atrioventricular junction in rodents, and acute (n=3) and chronic (4-week, n=6) electrophysiology studies were performed. Rodent toxicity studies (n=10) were performed. Electrical analysis of the CNTf-myocardial interface was performed. Results: In all cases, the large animal studies demonstrated improvement in conduction velocity using CNTf. The acute rodent model demonstrated ventricular preexcitation during sinus rhythm. All chronic cases demonstrated resumption of atrioventricular conduction, but these required atrial pacing. There was no gross or histopathologic evidence of toxicity. Ex vivo studies demonstrated contact impedance significantly lower than platinum iridium. Conclusions: Here, we show that in sheep, CNTfs sewn across epicardial scar acutely improve conduction. In addition, CNTf maintain conduction for 1 month after atrioventricular nodal ablation in the absence of inflammatory or toxic responses in rats but only in the paced condition. The CNTf/myocardial interface has such low impedance that CNTf can facilitate local, downstream myocardial activation. CNTf are conductive, biocompatible materials that restore electrical conduction in diseased myocardium, offering potential long-term restorative solutions in pathologies interrupting efficient electrical transduction in electrically excitable tissues. Abstract : Supplemental Digital Content is available in the text.